A Randomized Crossover Clinical Study Comparing the Effect of a Flat-Plane Nightguard Versus a Mandibular Advancement Device on Apnea-Hypopnea Index in Sleep Apnea Patients. - Kuehne, Cameron. (2017)
Abstract: Background: This randomized single blinded crossover clinical study tested the effect on subject's apnea-hypopnea index (AHI) wearing a flat-plane dental nightguard (NG) versus a mandibular advancement device (MAD). Materials and Methods: The sample consisted of 16 adults previously diagnosed with obstructive sleep apnea (OSA). Apnea-hypopnea indices were measured using a home sleep test unit administered at baseline, after one week of the nightguard, and one week of the MAD. A flat-plane nightguard, and a mandibular advancement device set at 60% of the subjects' maximum protrusion, were used. Results: A paired t-test analysis showed the difference in AHI between the two treatments was statistically significant (p=0.0025). Seven of 16 (43.75%) subjects experienced an increase of AHI by 2.23 events an hour while wearing the nightguard. Conclusion: The results of this study suggest that bruxism patients should be screened for OSA before fitting a nightguard, due to possible aggravation of OSA with nightguard usage. Dentists should consider use of a MAD instead of a nightguard for treating OSA, when appropriate.; Thesis (M.S.)--Tufts University, 2014.; Submitted to the Dept. of Other.; Advisor: Tofool Alghanem.; Committee: Leopoldo Correa, Paul Stark, Ron Kulich, and Noshir Mehta.; Keywords: Medicine, and Dentistry.